1983
DOI: 10.1093/oxfordjournals.jbchem.a134222
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Acid-Labile Sulfide in Cadmium-Binding Peptide 1 from Fission Yeast1

Abstract: Two kinds of Cd-binding peptides (Cd-BP1 and Cd-BP2) are induced in fission yeast upon addition of CdCl2 to the culture medium (l). It was also reported that Cd-BP1 and Cd-BP2 consisted of the same components, unit peptides (Cys3, Glu3, Gly1) and Cd atoms, though the respective amounts of components in each molecule were different (1, 2). Now, we have found that Cd-BP1 contains about 1 mol of acid-labile sulfide per mol, and Cd-BP2 contains no labile sulfide. The existence of the labile sulfide explains the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…However, when the complexes from tolerant cells were analyzed for acid-labile sulfide in preliminary studies (data not shown) by the method of King and Morris (12), very little could be detected. Indeed, a concentrated sample of complex partially purified from Cd tolerant cells yielded sulfide in the ratio of I to 38 mol Cd, much lower than that reported for S. pombe (14,18) even if it is considered that a mixture of complex I and complex II were present. These data indicate that there is either a difference in the sulfide content of complexes between S. pombe and D. innoxia or that something is interfering with the sulfide assay in our samples.…”
Section: Formation Of (-Yec)ng:cd Complexesmentioning
confidence: 65%
See 1 more Smart Citation
“…However, when the complexes from tolerant cells were analyzed for acid-labile sulfide in preliminary studies (data not shown) by the method of King and Morris (12), very little could be detected. Indeed, a concentrated sample of complex partially purified from Cd tolerant cells yielded sulfide in the ratio of I to 38 mol Cd, much lower than that reported for S. pombe (14,18) even if it is considered that a mixture of complex I and complex II were present. These data indicate that there is either a difference in the sulfide content of complexes between S. pombe and D. innoxia or that something is interfering with the sulfide assay in our samples.…”
Section: Formation Of (-Yec)ng:cd Complexesmentioning
confidence: 65%
“…This indicates that they consist of oligomers of the polypeptides. Murasugi et al (14) have shown that, in response to Cd, S. pombe synthesizes two types of ('yEC),G:Cd complexes, one of which contains acid-labile sulfide. Cdbinding by ('yEC)"G suggests its involvement in the mechanism of Cd detoxification.…”
mentioning
confidence: 99%
“…These features permit designation of this complex as the high-molecular-weight complex found in yeasts and other plants (Murasugi et al, 1983;Jackson et al, 1984;Mutoh and Hayashi, 1988;Reese et al, 1992;Speiser et al, 1992). Nothing in regions I1 and I11 indicated the presence of the less abundant sulfide-free, low-molecular-weight Cd-binding complex (Murasugi et al, 1983;Jackson et al, 1984;Kneer and Zenk, 1992). Perhaps a matrix other than Superose 12 would increase resolution in the low-molecular-weight range or the putative low-molecular-weight Cd-binding complex was not retained during anion-exchange chromatography and was absent for fractionation on Superose 12.…”
Section: Sulfide In Cd-binding Complexesmentioning
confidence: 99%
“…The Cd-binding complexes may be low and high molecular weight (Murasugi et al, 1983;Jackson et al, 1984;Kneer and Zenk, 1992). The high-molecular-weight complex is essential for sustained growth in high concentrations of Cd (Mutoh and Hayashi, 1988) and contains acid-labile sulfide (Murasugi et al, 1983;Speiser et al, 1992).…”
mentioning
confidence: 99%
“…'EC)nG (which has been referred to as phytochelatin, cadystin and class III MT), in response to elevated concentrations of certain toxic trace metals [20][21][22][23][24][25][26][27]. The pH of half-dissociation of Cd from complexes of (yEC),G isolated from Schi:o. saccharomyces pombe was 4.0 and 5.4, depending upon whether or not the complexes contained additional inor-Volume 292, number 1,2…”
Section: Omentioning
confidence: 99%